PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KARYAWAN PADA CV. GRAHA INDAH SARI - Rikkie Dekas (KOLEGIAL, 2019)
The influence of leadership style on employee motivation on CV. Graha Indah Sari" The research problem is as follows: Does leadership style influence employee motivation on CV. Graha Indah Sari? While the purpose of this research is to.know and analyze about: Effect of leadership style on employee motivation on CV. Graha Indah Sari. The research design used is associative research, which is to see the influence and relationship between independent variables consisting of: leadership style (X) with the dependent variable namely employee motivation (Y), and to test the hypotheses that have been formulated. The population in this study were employees of CV. Graha lndah Sari with 24 employees. Because the population is less than 200 people, the entire population will be used as research respondents. The research results obtained are 1). The relationship between leadership and employee motivation on CV. Graha Indah Sari is very close. 2). Leadership has a significant effect on motivation. This value is shown from the hypothesis test by using the r test, where the value of sig.r is greater than the value of r table which means the hypothesis that the motivation influences the leadership of the employee on CV. Graha lndah Sari is significant.